Failing Is Derailing: The Underperformance as a Stressor Model - Pindek, Shani (Frontiers in Psychology, 2020)
Job performance and job stress are widely studied phenomena in occupational research. However, most of the literature on the relationship between work stress and job performance conceptualizes job stress as an antecedent of performance, in line with the stress-performance framework, and does not examine what happens to the well-being of the employees after the performance was appraised as poor. In the current theoretical paper, I argue that task underperformance is a source of stress (i.e., stressor) for the employee, and as such can affect a wide range of employee outcomes. Task underperformance is conceptualized as comprised of two main types: acute/episodic underperformance such as a mistake or an accident (e.g., medical error, service failure), and chronic task underperformance such as not achieving the expected work products over time, with an interplay between these types. The source of the appraisal (objective, supervisor-rated, and self-rated underperformance) is also considered. Several disjoint literatures are then integrated in order to explain how underperformance is expected to result in subsequent decrements to employee well-being. At the chronic underperformance level, the following literatures are included: self-efficacy, negative effects of performance feedback, stress experienced when the basic need for competency is frustrated or when underperformance presents a threat to the self-image. At the acute/episodic level, affective and cognitive outcomes are explored and examples are drawn from several industries including service failures and medical errors. The interplay between the two types of underperformance, acute/episodic and chronic, is discussed, and then relevant moderators are offered. One notable moderator is the occupation-level consequences of error which likely affects most if not all outcomes. Finally, the discussion includes potential theoretical and practical implications for this conceptualization, as well as some methodological considerations for future research in this area.